Training of digital skills in Mechanical Engineering career in the University of Pinar del Rio "Hermanos Saíz Montes de Oca" - Yuslenia Sotolongo Rodríguez; Juan Lázaro Márquez Marrero (Revista MENDIVE, 2023)
The present work was directed to the improvement of the process of formation of digital skills to the professors of the Mechanical Engineering career of the University of Pinar del Río. The proposed objective was to determine the fundamentals of the process of training digital skills for professors of the Mechanical Engineering career at the University of Pinar del Río. To achieve this, the dialectical-materialist method was used as the guiding method, which allowed complementing the use of theoretical methods such as historical-logical, modeling and systemic-structural; Among the empirical methods, document analysis, survey and interview, and observation were used. The theoretical foundations for the training of digital skills for teachers of the Mechanical Engineering career at the University of Pinar del Río were determined; the principle of transversality, the transit through the different stages of the skill until it is internalized and the action of the internal structure of the skill, in each subject of the career curriculum, developing through actions and operations that coincide with the training Digital skills for teachers. Based on the proposed theoretical foundations, a cycle of methodological forms was structured for its implementation by fulfilling the methodological work of the Department of Mechanics of the University of Pinar del Río, being conceived from the methodology the formation of digital skills in this career.